Alteplase versus tenecteplase for thrombolysis after ischaemic stroke (ATTEST): a phase 2, randomised, open-label, blinded endpoint study. Issue 4 (April 2015) - Huang, Xuya; Cheripelli, Bharath Kumar; Lloyd, Suzanne M; Kalladka, Dheeraj; Moreton, Fiona Catherine; Siddiqui, Aslam; Ford, Ian; Muir, Keith W
Summary Background In most countries, alteplase given within 4·5 h of onset is the only approved medical treatment for acute ischaemic stroke. The newer thrombolytic drug tenecteplase has been investigated in one randomised trial up to 3 h after stroke and in another trial up to 6 h after stroke in patients selected by advanced neuroimaging. In the Alteplase-Tenecteplase Trial Evaluation for Stroke Thrombolysis (ATTEST), we aimed to assess the efficacy and safety of tenecteplase versus alteplase within 4·5 h of stroke onset in a population not selected on the basis of advanced neuroimaging, and to use imaging biomarkers to inform the design of a definitive phase 3 clinical trial. Methods In this single-centre, phase 2, prospective, randomised, open-label, blinded end-point evaluation study, adults with supratentorial ischaemic stroke eligible for intravenous thrombolysis within 4·5 h of onset were recruited from The Institute of Neurological Sciences, Glasgow, Scotland. Patients were randomly assigned (1:1) to receive tenecteplase 0·25 mg/kg (maximum 25 mg) or alteplase 0·9 mg/kg (maximum 90 mg). Treatment allocation used a mixed randomisation and minimisation algorithm including age and National Institutes of Health Stroke Scale score, generated by an independent statistician. Patients were not informed of treatment allocation; treating clinicians were aware of allocation but those assessing the primary outcome were not. Imaging comprised baseline CT, CT perfusion, and CT angiography; and CT plus CT angiography at 24–48 h. The primary endpoint was percentage of penumbra salvaged (CT perfusion-defined penumbra volume at baseline minus CT infarct volume at 24–48 h). Analysis was per protocol. This study is registered with ClinicalTrials.gov, number NCT01472926. Findings Between Jan 1, 2012, and Sept 7, 2013, 355 patients were screened, of whom 157 were eligible for intravenous thrombolysis, and 104 patients were enrolled. 52 were assigned to the alteplase group and 52 to tenecteplase. Of 71 patients (35 assigned tenecteplase and 36 assigned alteplase) contributing to the primary endpoint, no significant differences were noted for percentage of penumbral salvaged (68% [SD 28] for the tenecteplase group vs 68% [23] for the alteplase group; mean difference 1·3% [95% CI −9·6 to 12·1]; p=0·81). Neither incidence of symptomatic intracerebral haemorrhage (by SITS-MOST definition, 1/52 [2%] tenecteplase vs 2/51 [4%] alteplase, p=0·55; by ECASS II definition, 3/52 [6%] vs 4/51 [8%], p=0·59) nor total intracerebral haemorrhage events (8/52 [15%] vs 14/51 [29%], p=0·091) differed significantly. The incidence of serious adverse events did not differ between groups (32 in the tenecteplase group, three considered probably or definitely related to drug treatment; 16 in the alteplase group, five were considered drug-related). Interpretation Neurological and radiological outcomes did not differ between the tenecteplase and alteplase groups. Evaluation of tenecteplase in larger trials of patients with acute stroke seems warranted. Funding The Stroke Association.